Pethidine Versus Tramadol for Post-Anaesthetic Shivering Control in Patients Going Through Elective Surgery under Spinal Anaesthesia - Haq, Mazhar Ul; Ayaz, Saeed Bin; Qureshi, Sajjad; Rehman, Habib ur; ., Abdullah; Iftikhar, Hina (Pakistan Armed Forces Medical Journal, 2023)
Objective: To assess the efficacy of Pethidine versus Tramadol in controlling shivering after spinal anaesthesia in patients selected for lower limb surgery.Study Design: Quasi-experimental studyPlace and Duration of the Study: Department of Anaesthesiology, Combined Military Hospital, Multan Pakistan, from Jun 2019 to Dec 2020.Methodology: Seventy-four individuals (aged: 18 to 65 years) selected through non-probability consecutive sampling for elective lower limb orthopaedic procedures under spinal anaesthesia were included in the study. The patients were distributed among two groups through computer-generated random numbers to receive Tramadol at a dose of 0.5 mg/kg (Group-T) or Pethidine at 0.5 mg/kg (Group-P). The frequency of post-anaesthetic shivering was recorded in all patients.Results: The average age of patients in Groups T and P were 30.2 ± 9 years and 34.5 ± 10 years, respectively. Fifty (67.6%) patients were males, while 24(32.4%) were females. Post-anaesthetic shivering was reported in 37(78.7%) patients in the Tramadol- Group compared to 26(96.3 percent) patients in the Pethidine- Group (p = 0.041).Conclusion: Tramadol caused less post-anaesthetic shivering than Pethidine after spinal anaesthesia in our sample of patients undergoing lower limb surgery.